Respuesta :

Answer:

Equation for the function is:

f(x) = (3/2) · 2ˣ

Step-by-step explanation:

We have been provided with 2 points

Point 1 : (3, 12)

Point 2 : (4, 24)

Testing all three equations:

1) f(x) = 6/3 · 2ˣ

Substitute x of Point 1 in the equation

f(x) = (6/3) · 2³

f(x) = 16

y = 16 ≠ 12

NOT TRUE

Substitute x of Point 2 in the equation:

f(x) = (6/3) · 2⁴

f(x) = 32 ≠ 24

NOT TRUE

2) f(x) = 3/2· 2ˣ

Substitute x of Point 1 in the equation

f(x) = (3/2) · 2³

f(x) = 12

y = 12

TRUE

Substitute x of Point 2 in the equation:

f(x) = (3/2)· 2⁴

f(x) =  24

TRUE

3) f(x) = 2x

Substitute x of Point 1 in the equation

f(x) = 2(3)

f(x) = 6

y = 6 ≠ 12

NOT TRUE

Substitute x of Point 2 in the equation:

f(x) = 2(4)

f(x) = 8 ≠ 24

NOT TRUE

ACCESS MORE